Evaluación del impacto ambiental de residuos sólidos orgánicos, en un agroecosistema de (Ananas comosus) “Piña” en el fundo Pabloyacu - Paima Rodríguez. Gabi Gissela (2014)
This research work, presents information obtained during the months of December 2011 to September 2012, conducted with the aim to make the its solution for the benefit of the agricultura! production and the environment, it has been proposed to develop the research project called "Evaluation of the environmental impact of organic solid waste in an agroecosystem (Ananascomosus), "pineapple" in Pabloyacu farm, Moyobamba- 20 12 ". With the purpose of knowing the positive and negative impacts that shows the location of organic debris in the soil of an agroecosystem. The organic waste contributes to the growth and development of plant species, both directly and indirectly. Provide nutrients and store water, keep the humidity at the ground floor and serves as a refuge for invertebrates that act as biological controllers of sorne pests; inhibiting the growth and development of sorne weeds, among other benefits. However, the location of organic solid waste of chicken manure, sawdust, rice husks and household; in the fields of culture presents sorne disadvantages, such as the presence of odors, the transport of weed seeds and sorne exotic micro organic and phytophagous invertebrate. For this reason, it is intended to. implement the present research project, where he founded Pabloyacu of the Universidad Nacional de San Martín - Tarapoto, located 2 km from the city of Moyobamba. For such a motive, one tries to execute the present Investigation project, in Pabloyacu farm belong to San Martín National University - Tarapoto located to 2 km :from Moyobamba city. Key words: agricultura! production, environmental impact.